Large-area, size-tunable Si nanopillar arrays with enhanced antireflective and plasmonic properties. (24th June 2016) - Niu, Lihong; Jiang, Xiaohong; Zhao, Yaolong; Ma, Haiguang; Yang, Jingjing; Cheng, Ke; Du, Zuliang
Abstract: In this paper, a novel method using the modified Langmuir–Blodgett and float-transfer techniques was introduced to construct the perfect PS monolayer nanosphere template with large area up to cm 2 . Based on such templates, the diameter, length, packing density, and the shape of Si nanopillar arrays (Si NPAs) could be precisely controlled and tuned through the modified nanosphere lithography combined with a metal-assisted chemical etching (NSL-MACE) method. Manipulation of the etching time can effectively avoid permanent deformation/clumping to generate size-tunable Si NPAs. The optical properties of the Si NPAs can be controlled by the Si NPA morphologies resulting from the different reactive ion etching (RIE) time and chemical etching time. The enhanced antireflective property and electromagnetic field effect of Au/Si NPAs were proved by the results. The new modified NSL-MACE technique with the capability of scale-up fabrication of Si NPAs would be helpful for potential applications in optoelectronic devices.